Development and Application of 3D Visualization Submergence Analysis System for Datengxia Gorge - DENG Lisi; LIU Chuang; ZHU Changfu (Renmin Zhujiang, 2021)
In order to improve the 3D visualization level of the Datengxia Gorge Water Conservancy Project,solve the problems in management and retrieval of UAV aerial photography results,and meet the needs of high fidelity display of submerging area changes in the process of water level elevation in the reservoir area,this paper firstly sorts out and summarizes the background,objectives and tasks of system development and construction,builds the overall technical framework based on ArcGIS,and then discusses the key technical issues in building the framework in depth,finally develops the 3D visualization submergence analysis system of Datengxia Gorge.This system can realize the 3D display of data,quick retrieval and view,and estimation of submerging area.With good scientificity,practicability and reliability,it can assist to improve the intellectualization and humanization level of engineering construction management.Therefore,the system enjoys good practical application value.